2020
DOI: 10.21660/2020.70.9439
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temperature and Water Content on the Behavior of Soils

Abstract: The most widely used construction material for various civil infrastructures is the naturally available, compacted or modified soils. The behavior of these soils is significantly influenced by environmental factors such as the precipitation, evaporation and variations associated with the natural ground water table. The stability and deformation behavior are two key criteria that govern the design of these infrastructures. Soil is a complex material with different phases in unfrozen and frozen conditions. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…This form of adaptation is important, specifically in dealing with tidal effects on soil water content and soil temperature. Meanwhile, several studies showed that changes in soil temperature affect the bearing capacity of the pile foundation [10,11]. Gelam wood is a leading commodity and a potential source of local government revenue when managed properly.…”
Section: Utilization Pattern and Potential Of Gelam Wood (Melaleuca C...mentioning
confidence: 99%
“…This form of adaptation is important, specifically in dealing with tidal effects on soil water content and soil temperature. Meanwhile, several studies showed that changes in soil temperature affect the bearing capacity of the pile foundation [10,11]. Gelam wood is a leading commodity and a potential source of local government revenue when managed properly.…”
Section: Utilization Pattern and Potential Of Gelam Wood (Melaleuca C...mentioning
confidence: 99%